Aquatic photolysis of 2, 4-dichloro-6-nitrophenol—the toxic nitrated byproduct of 2, 4-dichlorophenol. (March 2022) - Li, Yunong; Qin, Hao; Wang, Lixiao; Lu, Junhe; Chovelon, Jean-Marc; Zhou, Quansuo; Ji, Yuefei
Abstract: 2, 4-Dichloro-6-nitrophenol (DCNP) is a toxic nitrated byproduct of 2, 4-dichlorophenol (2, 4-DCP) commonly found in agriculturally impacted waters (e.g., paddy waters). DCNP has both genotoxicity and developmental toxicity and can cause endocrine disrupting effects on aquatic species. Herein, we investigated the photolysis of DCNP under UV254 irradiation in aqueous solutions. Results show that the anionic form of DCNP (DCNP − ) is more photoreactive than the neutral form (DCNP 0 ) due to its higher molar absorption coefficient and quantum yield. The presence of Suwannee River natural organic matter (SRNOM) inhibits the direct photolysis of DCNP through light screening. A series of photoproducts were identified by solid phase extraction (SPE) and high resolution-mass spectrometry (HR-MS) analysis. The photolysis of DCNP generates several photoproducts, including photoreduction, photonucleophilic substitution, photoionization, and dimerization intermediates. The primary photochemical mechanisms include photoionization from the singlet state and heterolytic C–Cl bond splitting in the triplet state. This contribution may shed some light on the photochemical transformation and fate of DCNP in UV-based engineering systems or natural sunlit surface waters. Graphical abstract: Image 1 Highlights: Exposure to UV254 resulted in fast decay of DCNP in neutral aqueous solution. Anionic form of DCNP was the most photoreactive species. The presence of SRNOM inhibited the direct photolysis of DCNP. Several photoproducts were identified by SPE-HR-MS analysis. Photoionization and photo-dehalogenation were involved in DCNP photolysis.